THE STUDY OF TPR IMPLEMENTATION IN TEACHING LISTENING AND SPEAKING FOR ELEMENTARY SCHOOL AT SD LABORATORIUM UNDIKSHA SINGARAJA IN THE ACADEMIC YEAR 2013/2014 - Prananti, A; Ratminingsih, M; Marjohan, A (Jurnal Pendidikan Bahasa Inggris undiksha, 2019)
AbstractThis study was a descriptive qualitative research, which aimed to find out the implementation of TPR method for teaching listening and speaking, the reasons why the teacher chose TPR method and what the problems were faced by the teacher in implementing TPR method for teaching listening and speaking. The subjects of the study were the English teacher and the 32 students Class 5A, SD Laboratorium Undiksha Singaraja.  This study was in the form of case study. The data were collected by using four instruments, interview guide, observational checklist, recorders and test in order to prove the teacher’s statement about students’ improvement. The data obtained were then analyzed descriptively. There were three main processes of data analysis: data reduction, data display and drawing conclusion/ verification. From the overall findings, it can be concluded that TPR method was implemented in accordance to the theory conceptualized by Larsen-Freeman (2000) and Richards & Rodgers (2001) and was combined with songs.  Based on the teacher’s statement and test result, the reasons why TPR method was used because it made students enjoy the class, easy to understand the material and teacher considered TPR method was effective to improve students’ ability in listening and speaking. However, there were few problems faced by the teacher in implementing TPR for teaching listening and speaking, namely: The students’ characteristic affects their confidence in TPR activities, and TPR was not flexible to be implemented for all materials and students’ levels.                                  Keywords: TPR Method, Listening, Speaking